Research progress and strategies for vaccines and targeted drugs against highly virulent porcine epidemic diarrhea virus - Wang, Qiuxuan; Liu, Songrui; Chen, Hongrui; Liu, Xuanyi; Zhang, Hanjia; Wang, Xuehui; Meng, Qingfeng; Dong, Hao (Frontiers in Microbiology, 2025)
As an acute and highly contagious enteric disease of swine, porcine epidemic diarrhea virus (PEDV) has caused high piglet mortality and significant economic losses. Commercialized vaccines provide only partial cross-protection against the novel, highly virulent PEDV strains. Developing new vaccines against highly virulent PEDV strains would help protect the pig industry from the serious challenges posed by novel, highly virulent PEDV infections. Natural compounds and chemical and biochemical source-targeted drugs designed to act on specific proteins, enzymes, or mechanisms can complement each other’s advantages when used in combination, thereby enhancing the effectiveness of drug-based prevention in the control of highly virulent PEDV. Drugs targeting Toll-like receptor 3 (TLR3) can aid vaccines to compensate for interferon (IFN) secretory deficiencies to protect pigs from highly virulent PEDV infection. This review summarizes recent progress in the development of vaccines against highly virulent PEDV, natural compounds, and chemical and biochemical source-targeted drugs that have been explored in cell and pig models with clearly defined mechanisms. It also aims to provide comprehensive strategies for the prevention and control of highly virulent PEDV infections in pigs.